Accessibility, Equity, and Mode Share: A Comparative Analysis Across 11 Canadian Metropolitan Areas - Boer Cui; Ahmed El-Geneidy (Findings)
Accessibility impacts mode choice and the degree of its impact varies between geographic regions and income groups. This paper presents an introductory analysis of this relationship for low and higher-income groups across 11 Canadian metropolitan areas. In all regions, low-income groups exhibit higher public transport use at the same level of accessibility. Additional differences exist between income groups in different regions when considering the change in mode share with varying accessibility. This study, while demonstrating the link between public transport mode share and accessibility, also begets further research to explain the differences in this relationship between groups in different regions.